Clarifying the association between Parkinson’s disease and vitiligo: a population-based large-scale study - Kridin, Khalaf; Ofir, Lior; Weinstein, Orly; Badarny, Samih (Frontiers in Neurology, 2024)
Objective: Our knowledge about the association between vitiligo and Parkinson's disease (PD) is sparse.We sought to investigate the bidirectional epidemiological association between vitiligo and PD.A population-based study was conducted using Clalit Health Services (CHS) database (2002-2019) using both a cohort study and a case-control study design. Adjusted hazard ratio (HR) and odds ratio (OR) were calculated by multivariate Cox and logistic regressions, respectively.Results: Overall, 20,851 vitiligo patients and 102,475 controls were included. The incidence of new-onset PD was 2.9 (95% CI, 2.1-4.1) and 4.3 (95% CI, 3.8-4.9) cases per 10,000 person-years among patients with vitiligo and controls, respectively. Patients with vitiligo had a significantly decreased risk of developing new-onset PD (adjusted HR, 0.62; 95% confidence interval [CI], 0.43-0.89, P=0.009). On the other hand, the likelihood of having vitiligo after a preexisting diagnosis of PD was not statistically different (adjusted OR, 0.80; 95% CI, 0.61-1.06; P=0.117). Relative to the remaining patients with vitiligo, those with vitiligo and comorbid PD experienced an elevated risk of all-cause mortality (adjusted HR, 2.63; 95% CI, 1.82-3.80; P<0.001) and higher prevalence of cardiometabolic comorbidities.Vitiligo is associated with a lower risk of developing PD. The presence of comorbid PD predisposes patients with vitiligo to elevated mortality and cardiometabolic outcomes.